Autobiographical Memory Impairment in Adolescents in Out-of-Home Care - Jimeno, María Verónica (Journal of interpersonal violence, 2021)
Childhood maltreatment is a major risk factor for emotional problems in adolescence and adulthood and has deleterious effects on cognitive functions such as working memory. A key aspect in the study of the cognitive and affective consequences of maltreatment is autobiographical memory, especially regarding the difficulty retrieving specific memories, known as overgeneral memory. In this study, autobiographical memory tests, working memory, and a depressive symptom assessment were administered to 48 adolescents in care with a history of maltreatment (22 abused and 26 neglected) without mental disorder, who had been removed from their family and were living in residential child care, and to 61 adolescents nonmaltreated who had never been placed in care. The results show that adolescents with a history of maltreatment remember fewer specific events (Cohen d = 1.1–1.3) and that both working memory and depressive symptoms are involved in overgeneral memory (R2 = .13–.26). Directions for future research include neuropsychological assessment and implementation of a training program to increase specific memory recall in this population.